Baghdad's batterie and the south and northern epistemologies: a narrative review (Research, Society and Development, 2020)
The present work aims to present a narrative review of the Epistemologies of the North and the Epistemologies of the South, referring to the authorship of the discovery of the electric cell, based on the proposals presented by the Portuguese sociologist Boaventura de Sousa Santos in his text entitled “A discourse on the sciences in the transition to a postmodern science ”(Santos, 1988) and in his video discourse posted on the YouTube website (Santos, 2016). As a starting point for these notes by Boaventura Santos, it is clear that the dominant Northern Epistemology does not allow Southern Epistemology to stand out and materialize. To corroborate this statement, we present academic and scientific works that value only Northern Epistemology, denying the existence of Southern Epistemology, as well as works that present the existence of Southern Epistemology without giving its real value, and finally, a work that presents the Epistemology of the South as something concretized and with scientific evidence. The review found that the reflection and discussion of existing knowledge in Southern Epistemologies can contribute to Science Education that focuses on the formation of more reflective citizens, with more active attitudes in society, and actively contribute to social transformation, so that Epistemologies of the South are featured in teaching practices carried out in Brazilian classrooms.